2021
DOI: 10.1186/s40794-021-00157-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of enterotoxigenic Escherichia coli toxins and colonization factors in children under five years with acute diarrhea attending Kisii Teaching and Referral Hospital, Kenya

Abstract: Background Enterotoxigenic Escherichia coli (ETEC) is one of the leading causes of infectious diarrhea in children. There are no licensed vaccines against ETEC. This study aimed at characterizing Escherichia coli for ETEC enterotoxins and colonization factors from children < 5 years with acute diarrhea and had not taken antibiotics prior to seeking medical attention at the hospital. Methods A total of 225 randomly selected archived E. coli strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
2
7
1
Order By: Relevance
“…In our study, 33.3% of ETEC isolates produced heat-stable toxins (STs), 12.8% produced heat-labile toxins (LTs), and 7.7% produced both enterotoxins. These findings are consistent with those of a study conducted in Kenya [ 70 ] and Indonesia [ 71 ], where ST toxins were the most common, followed by LT, and both enterotoxins were the least common. In contrast, studies from Iran [ 72 ] and Bolivia [ 73 ] found that LT toxins were detected at a higher rate than ST toxins.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 33.3% of ETEC isolates produced heat-stable toxins (STs), 12.8% produced heat-labile toxins (LTs), and 7.7% produced both enterotoxins. These findings are consistent with those of a study conducted in Kenya [ 70 ] and Indonesia [ 71 ], where ST toxins were the most common, followed by LT, and both enterotoxins were the least common. In contrast, studies from Iran [ 72 ] and Bolivia [ 73 ] found that LT toxins were detected at a higher rate than ST toxins.…”
Section: Discussionsupporting
confidence: 92%
“…The discrepancy between our findings and those of other studies could be attributable of variation in CF expression by ETEC in different geographical regions, as well as differences in laboratory methods/primers used to identify CFs [46]. In addition, due to sub cultured repeatedly or storage for long term, the plasmid containing the CF genes has been lost [44]. Decreasing the expression of CF genes, a mutation inside the genetic locus, and expression of a CF not covered by the primers used in the PCR panel [6], [57], [58].…”
Section: Detection Of Colonization Factorscontrasting
confidence: 96%
“…Variations in our results with other researches could be related to changes in primers utilized, geographical considerations, population targeted, and sample size [44]. In nine of the 12 research conducted in Africa, 22 of 34 investigations in Asia, and three of six studies in Latin America and the Caribbean, ETEC was being the first or second most often isolated pathogen [45].…”
Section: Identification Of Etec Toxinsmentioning
confidence: 72%
“…ETEC strains are characterized by heat-labile (LT) and/or heat-stable (ST) enterotoxins which are plasmid-encoded (6,7). In developing nations, enterotoxigenic E. coli is a known causal agent of diarrhea in travelers and children (8,9).…”
Section: Introductionmentioning
confidence: 99%